A thermosensitive chitosan‐based hydrogel for sealing and lubricating purposes in dental implant system. (1st March 2019) - Cao, Xiaoxiao; Cai, Xinjie; Chen, Ruiying; Zhang, Huimei; Jiang, Tao; Wang, Yining
Abstract: Background: Mechanical and biological complications associated with implant systems happen frequently in the clinic. Purpose: To develop a chitosan (CS)‐based thermosensitive hydrogel for sealing and lubricating purposes in dental implant system. Materials and Methods: In this study, a thermosensitive hydrogel made up of CS, β‐glycerophosphate pentahydrate (β‐GP), and povidone‐iodine (PVP‐I), called CS/β‐GP/PVP‐I thermosensitive hydrogel, was fabricated. Three experimental groups with different volume ratios of CS to β‐GP were prepared, namely 16/4, 13/7, and 10/10 groups. The surface topography of the different groups and their physicochemical characteristics were examined by SEM, FTIR, and X‐ray diffraction analysis. The cytotoxicity of the hydrogel was examined by CCK‐8 test. In vitro antibacterial efficiency was analyzed by the spread plate method. Sealing ability was detected by incubating two‐piece implants in Escherichia coli suspension. Lubricating ability of the hydrogel was evaluated by the removal torque test with a calibrated digital torque meter. Results: The CS/β‐GP/PVP‐I thermosensitive hydrogel was fabricated and showed a highly porous structure under SEM. An in vitro cytotoxicity test demonstrated that 13/7 group displayed no cytotoxicity. Furthermore, all three groups showed obviously antibacterial effects. In the sealing ability test, 16/4 group showed the best sealing ability. The removal torque of 16/4 group and 13/7 group was significantly greater than control group. Conclusions: Based on our findings, it could be concluded that the thermosensitive and antibacterial CS/β‐GP/PVP‐I hydrogel with sealing and lubricating ability was successfully prepared. The hydrogel had better sealing and lubricating effects when the volume ratio of CS to β‐GP was 16/4.